Analisis Kekuatan Struktur Retak Skin Fuselage Repair Pesawat B747-400 - Djarot Wahju Santoso (Institut Teknologi Dirgantara Adisutjipto, 2016)
Abstract — Structure Repair Manual (SRM) is a manufacture guidelines issued by the MRO (Maintenance and Repair Organization) who have the authority to perform a repair aircraft. SRM function as an actual reference in doing a modification SRM repair. In its application modifications can be done by changing the layout variations and variations of fastener used. To determine the feasibility of a repair configuration modifications done by modeling and analysis to determine the maximum stress that occurs in both configurations. In this research, modeling and analysis using software CATIA V5R21. Created 2 configuration model that SRM structure repair and modification of the structure of SRM repair. Both models are given internal pressure load, while the fastener strength was tested by making a simpler model to provide tensile load.The maximum stress that occurs in structures that modification SRM repair is 18265 Psi by the internal pressure loading, whereas for tension loading cases amounted to 22380.9 Psi. Based on the margin of safety the modifications structure of SRM repair declared to be safer than SRM structure repair. Keywords : skin fuselage, repair, crack, SRM